Компьютерное моделирование гемодинамики в искривленных сосудах - Зенин, О.К.; Оверко, В.С.; Бескровная, М.В.; Брюханов, В.М.; Руденко, М.Г. (Таврический медико-биологический вестник, 2013)
Проведено математичне моделювання течії крові у змінених судинах. Комп’ютерне моделювання було
проведено для трьох конфігурацій: 1) слабка ступінь кривизни (вертикальний розмір більше горизонтального),
2) середній ступінь кривизни (вертикальний розмір дорівнює горизонтальному), 3) сильна ступінь кривизни
(горизонтальний розмір більше вертикального). Досліджено вплив типу викривленості на інтенсивність та
особливості вторинної та зворотної течії крові в судинах у різні моменти часу кардіального циклу. Також
були розраховані втрати тиску на скривленої ділянці та амплітуді пульсацій тиску на початку, в середині та
виході зі скривлення. Mathematical simulation of the blood flow in the curved blood vessels has been performed. Simulations are
made for three different configurations of the blood vessels: 1) the weak level of curvature (vertical size exceeds
the horizontal one), 2) the average level of curvature (the vertical size and the horizontal one are equal), 3) the
strong level of curvature (the horizontal size exceedsthe vertical one). We have investigated the curvature type
influence on the intensity and features of the secondary and reverse blood flows in the vessels at different moments
of the cardiac cycle. In addition, we have calculated the pressure loss at the curvilinear part and the amplitude of
pressure pulsations in the beginning, in the middle and the output of the curvature.